PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPESTUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS II SDN 014 SILIKUAN HULUKECAMATAN UKUI KABUPATEN PELALAWAN - ', Ritmiyati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low learning outcomes IPA grade II SDN 014 Silikuan Hulu, Of the 27 students who completed the results of their study only 12 students or 44.5% while the average value of student learning outcomes is 64.4 of learning outcomes is still low by KKM set is 70. Based on this the researchers conducted a study class action by implementing cooperative learning model type STAD with the aim to improve learning outcomes IPA. This study was conducted by two cycles, each cycle consisting of two meetings and one daily tests. The instruments used were observation sheet activities of teachers and students and science achievement test. The data collection technique used is the technique of observation and testing techniques. The results showed that after implementation of cooperative learning model STAD teacher and student activity increased in the first cycle of the first meeting of teachers categorized moderate activity, with a total score of 16 or 66.7%. At the second meeting increased with a total score of 18 or 75% in both categories. At the first meeting of the second cycle of the total score increased to 21 or 87.5% in both categories. Furthermore, at the second meeting increasing with a total score of 22 or 91.7% and categorizing them very well. Activities of students has increased at each cycle. In the first cycle of the first meeting and the second meeting of student activity is average, with a total score of the first meeting of 14 or 58.3%, and the second meeting a total score of 16 or 66.7%. In the second cycle the first meeting of the total score increased to 20 or 83.3% in both categories. Furthermore, at the second meeting increasing with a total score of 22 or 91.7% and categorizing them very well. Besides learning outcomes IPA also increased on the basis of the average scores of learning outcomes was 64.4. In the first cycle increased to 79.8. In the second cycle the average value increased to 84.3. Besides classical completeness in each cycle to increase the initial data completeness students 44.4% or 12 students. In the first cycle the number of students who pass are 21 students or 77.8%. In the second cycle students' mastery learning increased with 26 students or 96.3%. It shows in the classical class is also declared complete.